Instagram Carousel Content Effectivity in of Micro-Entrerprise Promotion Strategy - Arief Zul Fauzi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2026)
This study aims to examine the effectiveness of carousel content in promoting Micro, Small, and Medium Enterprises through Instagram. The research subject is the Instagram account owned by Toko Swara (TSW Gifts), a Micro-Enterprise that markets traditional clay teapots (poci) as a signature souvenir from Tegal. Using a quantitative approach with a pretest–treatment–post-test design, the study measured promotional performance before and after the use of carousel content based on Instagram Insights. The results showed an increase in content performance following the use of carousel. The average reach nearly doubled, and the engagement rate rose from 14.84% to 26.10%. These findings indicate that carousel content can drive audience engagement more effectively than regular posts. This study recommends carousel content as a relevant and impactful promotional strategy, especially for Micro-Enterprise with limited follower bases.